Diversion Taken for the Case of Violence Committed by Children - Haris, Haris; Santi, Nyadina Eka (Indonesia Law Reform Journal, 2024)
This research seeks to investigate, study, and analyse the diversion taken in the case of violence committed by children in the Sub-Regional Police Department in Malang City. This is socio-empirical research entailing direct observation in the Sub-Regional Police Department in Malang City, aiming to delve into the problems discussed. The research materials consist of primary and secondary data obtained directly and indirectly. The analysis results reveal that the process of diversion in the case of violence committed by children should take into account deliberation involving both victims and perpetrators along with their parents/guardians, social welfare personnel, and the members of the public. Some measures of diversion work as expected when redress could be obtained, while others fail when family members of the victims insist on bringing the case to court. The diversion process should also take into account mentorship for the victims and their rights, where direct protection is provided. A legal advisor or a psychologist can facilitate this mentorship. Diversion is intended to teach children to be responsible for what they have committed to ensure that the objectives of diversion enshrined in the Law concerning the Judicial System of Juvenile Crime are attained. Abstrak Penelitian ini bertujuan untuk mengetahui, mengkaji, dan menganalisis diversi yang dilakukan dalam kasus kekerasan yang dilakukan oleh anak di wilayah hukum Polres Kota Malang. Penelitian ini merupakan penelitian sosio-empiris dengan melakukan observasi langsung di Kepolisian Sektor Kota Malang, yang bertujuan untuk mendalami permasalahan yang dibahas. Bahan penelitian terdiri dari data primer dan sekunder yang diperoleh secara langsung dan tidak langsung. Hasil analisis menunjukkan bahwa proses diversi dalam kasus kekerasan yang dilakukan oleh anak harus memperhatikan musyawarah yang melibatkan korban dan pelaku beserta orang tua/wali, tenaga kesejahteraan sosial, dan masyarakat. Beberapa langkah diversi berhasil seperti yang diharapkan ketika ganti rugi dapat diperoleh, sementara yang lain gagal ketika anggota keluarga korban bersikeras untuk membawa kasus tersebut ke pengadilan. Proses diversi juga harus mempertimbangkan pendampingan bagi para korban dan hak-hak mereka, di mana perlindungan langsung diberikan. Seorang penasihat hukum atau psikolog dapat memfasilitasi pendampingan ini. Diversi dimaksudkan untuk mengajarkan anak untuk bertanggung jawab atas apa yang telah mereka lakukan untuk memastikan bahwa tujuan diversi yang tercantum dalam Undang-Undang Sistem Peradilan Pidana Anak tercapai.